Structural Strengthening using Carbon Fiber Reinforced Polymer - Hartono . (Civil Engineering Dimension, 2012)
This paper presents practical pointers to be considered in strengthening concrete structure with Carbon Fiber Reinforeced Polymer (CFRP) which becomes more popular nowadays. It is pointed out that the strengthening process consists of assessment, design, and installation andthat should be done by people who are competent, experienced, and professional in their field.